TEKNIK PEMBERIAN BALIKAN DALAM MENINGKATKAN HASIL BELAJAR SISWA IPA DIMASA PENDEMI COVID-19 - Giarti Manopo; Suleman Suleman (LPPM Universitas Muhammadiyah Gorontalo, 2021)
This research is an action class research with used giving feedback technique to increase learning outcomes of science Subject. The problem is whether the application of feedback giving techniques can improve science learning outcomes during the Covid-19 pandemic. The objective to describe the science learning process during Covid-19 Pandemic which Applicated giving feedback technique in science learning in V class of SDN 1 Bone Raya. The results based on the implementation of the first cycle class action only 50% or 6 people who achieved the minimum completeness criteria (KKM) ≥ 75 with indicators of learning achievement reaching 71.67%. In the second cycle, it increased to 10 people or 83% who reached the minimum completeness criteria (KKM) 75 with learning outcomes indicators of 89.16%. Based on these results, the use of feedback giving techniques can improve science learning outcomes in Class V SDN 1 Bone Raya, Bone Bolango Regency.Penelitian merupakan Penelitian Tindakan Kelas (PTK) dengan menggunakan Teknik Pemberian Balikan untuk meningkatkan hasil belajar IPA. Permasalahan apakah dengan penerapan teknik pemberian balikan dapat meningkatkan hasil belajar IPA di masa pandemi covid-19. Tujuan penelitian ini adalah mendeskripsikan proses pembelajaran IPA dimasa Pandemi yang menerapkan Teknik Pemberian Balikan pada pembelajaran IPA di Kelas V SDN 1 Bone Raya Kabupaten Bone Bolango.Hasil penelitian pada pelaksanaan tindakan kelas siklus I hanya 50% atau 6 orang yang mencapai criteria ketuntasan minimal (KKM) ≥ 75 dengan indicator capaian hasil belajar mencapai 71,67%. Pada siklus II meningkat menjadi 10 orang atau 83% yang mencapai criteria ketuntasan minimal (KKM) ≥ 75 dengan indicator capaian hasil belajar 89,16%. Berdasarkan hasil penelitian tersebut penggunaan teknik pemberian balikan dapat meningkatkan hasil belajar IPA di Kelas V SDN 1 Bone Raya Kabupaten Bone Bolango.